Prevalence of Obesity and its Influencing Factors in Affluent School Children of Tumkur: Lessons from South India - Kumar, Sunil; Amruth, M.; Kumar, Prashant; Balakrishna, A.G.; Prabhudeva, M.C. (International Journal of Child Health and Nutrition, 2015)
Background: Obesity is defined by WHO “as a condition of abnormal or excessive fat accumulation in adipose tissue, to the extent that health may be impaired”. The problem of childhood obesity is quite high in rich and affluent countries. To estimate the prevalence of obesity among school children aged 6-15 years in three affluent schools of Tumkur. To study the influencing factors of obesity among school children. Methods: Study Design: Case Control study. Study Settings: Three affluent schools of Tumkur city, Karnataka, South India. Sample size was 2000 Students of three affluent schools and duration of study was from June to August 2014. Each Child’s height and weight were measured by adopting standard procedure. Body mass index (BMI) was calculated using BMI charts based on NCHS (national center for health statistics) standards. A child was considered obese if the BMI was > 95th percentile cutoff point which is specific to the age and sex of the child. To determine the association of (life style) influencing factors of obesity in children, mothers were interviewed in presence of children to gather information’ about their child’s daily (24 hour) activity. Results: Out of 2000 children 66 were obese. The prevalence was 3.3% in school children in the age group of 6-15 years in three affluent schools of Tumkur. In our study, Prevalence of obesity was more in boys (3.47%) on comparison to girls (3.04%). There is increased prevalence of obesity in age group of six, eleven and twelve years. In this study 77.2% cases spent less than 2 hrs in a day and 22.7% cases spent more than 2 hrs in physical activities. Prevalence of obesity was more in children who spent less than 2 hrs in a day in physical activities. This was statistically significant. Conclusions: Prevalence of obesity in school children aged 6-15 yrs is 3.3% in three affluent schools of Tumkur. Prevalence of obesity was more in boys on comparison with girls. Physical activity was the significant influencing factor of obesity among school children.